Ambient Seismic Source Inversion in a Heterogeneous Earth: Theory and Application to the Earth's Hum. Issue 11 (27th November 2017) - Ermert, Laura; Sager, Korbinian; Afanasiev, Michael; Boehm, Christian; Fichtner, Andreas
Abstract: The sources of ambient seismic noise are extensively studied both to better understand their influence on ambient noise tomography and related techniques, and to infer constraints on their excitation mechanisms. Here we develop a gradient‐based inversion method to infer the space‐dependent and time‐varying source power spectral density of the Earth's hum from cross correlations of continuous seismic data. The precomputation of wavefields using spectral elements allows us to account for both finite‐frequency sensitivity and for three‐dimensional Earth structure. Although similar methods have been proposed previously, they have not yet been applied to data to the best of our knowledge. We apply this method to image the seasonally varying sources of Earth's hum during North and South Hemisphere winter. The resulting models suggest that hum sources are localized, persistent features that occur at Pacific coasts or shelves and in the North Atlantic during North Hemisphere winter, as well as South Pacific coasts and several distinct locations in the Southern Ocean in South Hemisphere winter. The contribution of pelagic sources from the central North Pacific cannot be constrained. Besides improving the accuracy of noise source locations through the incorporation of finite‐frequency effects and 3‐D Earth structure, this method may be used in future cross‐correlation waveform inversion studies to provide initial source models and source model updates. Plain Language Summary: The Earth's hum is a low‐frequency, background seismic signal excited by the interplay of long periodic ocean waves with the Earth's solid crust. We present the first real‐data application of a new localization technique for the sources of hum, which can be used for similar ambient sources in future studies. This technique can account for realistic wave propagation effects of seismic waves in the Earth. This is achieved by storing simulated responses of the Earth to impulsive sources, so‐called Green's functions, in order to use them during localization. Our results confirm previous findings that the sources of the Earth's hum vary seasonally, occurring at Pacific coasts or shelves and in the North Atlantic during North Hemisphere winter, as well as South Pacific coasts and several distinct locations in the Southern Ocean in South Hemisphere winter. Our results also appear to indicate that hum sources are rather localized in space. Key Points: We apply gradient‐based ambient noise source inversion to long periodic "hum" cross correlations The inversion procedure fully accounts for heterogeneous Earth structure and finite‐frequency sensitivity Hum sources appear persistent and narrowly localized at coasts or shelves and high bathymetry